Análise e aplicação de índices de sustentabilidade em bacias hidrográficas - estudo de caso: sub-bacia do Ribeirão Onça, MG - Anderson Paulino de Souza (2020)
The intensification of socioenvironmental problems caused by human activities emphasized the fact that natural resources are limited and their indiscriminate use compromises the sustainability of the Earth resources. This study aims to analyze and apply the methodological foundations of the main sustainability measurement tools in the socio-environmental diagnosis of the Ribeirão Onça watershed, as well as to identify the potentialities and weaknesses of the use of indexes in complex multidisciplinary decision-making processes. The study is justified by the fragmented dissemination of works related to the application of sustainability assessment tools directed to watersheds, and aims to provide elements that allow a better understanding of the pertinence and feasibility of using systems of sustainability indicators in this territorial delimitation. For the development of the work, four internationally recognized sustainability assessment methods were selected - Ecological Footprint (PE), Sustainability Panel (PS), Sustainability Barometer (BS) and Watershed Sustainability Index - WSI - that were applied to the study of a specific territorial area, the Ribeiro Onça watershed. Inserted in the Rio das Velhas watershed and integrated by the municipalities of Belo Horizonte and Contagem (MG), the region is characterized by a high level of urbanization, pollution, and a low level of quality of water resources. The research was guided by the following steps: literature review, selection of indicators for the application of sustainability analysis tools; consultations with researchers and entities responsible for developing the indexes; and verification of results with the socio-environmental diagnosis available in the Rio das Velhas Basin Water Resources Master Plan (PDRH-Velhas). In general, sustainability assessment results obtained for Ribeirão Onça sub-watershed, with the exception of those obtained by the PE tool (focus on consumption), proved to be compatible: PE, ecological deficit (unsustainable); PS, medium level of sustainability; BS, intermediate level of sustainability; WSI, intermediate level of sustainability. Despite the methodological differences between the tools, they were effective in identifying the most critical problems (quality of water resources) and improvements in socioeconomic perspectives in the region in the analyzed period (2010-2014). In addition, results obtained by the applied methods are peculiar and have strong indications of complementarity, so that the use of one index does not invalidate another. In a complementary way, an Artificial Intelligence (Fuzzy) technique was applied to assess the region, resulting in an intermediate level of sustainability, consistent with the PS, BS and WSI methods. In the context of the Ribeirão Onça sub-watershed, the evaluation results obtained were plausible to reality, with some of the socioenvironmental aspects identified having a direct / indirect relationship with the socioenvironmental programs and their respective budgets arranged in the PDRH-Velhas action plan, demonstrating the potential of the tools used in this research to assist in decision-making processes and diagnostics of watersheds.